PHYSICOCHEMICAL CHARACTERIZATIONS, DISSOLUTION BEHAVIOR AND RELEASE KINETICS OF CURCUMIN AND β-CYCLODEXTRIN MOLECULAR INCLUSION COMPLEXES - M.J. ANSARI; M.M.AHMED (International Journal of Pharma and Bio Sciences, 2015)
This paper presents physicochemical characterization, dissolution behavior and release kinetics of curcumin and its molecular inclusion complexes with β-cyclodextrin. Solid inclusion complexes of curcumin with β-cyclodextrin in 1:2 molar ratios were prepared by grinding, kneading and freeze drying methods. Complexes were characterized by differential scanning calorimetry, infra red spectroscopy and X-ray diffractometry. Prepared inclusion complexes were compared with pure curcumin for their dissolution behavior. The dissolution study demonstrated only 10.5% release from pure curcumin at 1 hour as opposed of approximately 30-35% release form curcumin complexes. At least 3 fold increases in dissolution of all tested complexes were observed at one hour as compared to pure curcumin, with a maximum increase of approximately 3.5 fold as shown by kneaded and freeze dried complexes. At the end of 6 hours, approximately 75-80% release was observed from all inclusion complexes with a maximum release of 80% exhibited by freeze dried complex. The release of the curcumin from all inclusion complexes was observed to follow the first order release kinetics, since the correlation coefficient for the first order was higher in comparison to other tested models.